Approaching the wicked problem of obesity: an introduction to the food system compass. Issue 4 (5th October 2017) - Parkinson, Joy; Dubelaar, Chris; Carins, Julia; Holden, Stephen; Newton, Fiona; Pescud, Melanie
Abstract : Purpose: The purpose of this paper is to focus on food consumption as part of the wicked problem of obesity. Specifically, the authors seek to explore the complex interplay between stakeholders such as food producers, marketers, health and medical practitioners and policymakers and their influence on the ways in which individuals consume food and also chart a course forward using a systems approach, social marketing techniques and social enterprise to develop solutions to effect change. Design/methodology/approach: This is a conceptual paper that proposes the food system compass to understand the complex interplay between stakeholders. Findings: This new tool will provide social marketers with an improved understanding of the complexity of interactions between stakeholders and outcomes and integrating the necessity for coordination within and across micro, meso, exo and macro levels of the system as well as across sectors, institutions and stakeholders. Research limitations/implications: This is a conceptual paper and proposes the food system compass which offers a foundation for future research to expand upon. Originality/value: This paper seeks to advance the theoretical base of social marketing by providing new insights into the trans-disciplinary and dynamic circumstances surrounding food consumption and obesity and highlights leverage points where joint actions can be facilitated with actors across and between micro, meso, exo and macro levels.